Let's Personify School History. Several Reasons for the Systematic Inclusion of Oral History and Ego-history into Didactics of History. - Moravkova, Nadezda (Civilia, 2017)
Possibilities of work with the witnesses and possibilities of ego-history in the didactics of history are considerable and still full of challenges. The paper describes the methodological occasions in combination of classical educational media and oral historical documents in teaching school history. It is about importance of oral history for teaching in general. Contribution consists mainly in personalization of school history, a defence against a black and white perception of the past or in mediating an authentic historical record in the history of everyday life. But it is also address to the difficulties which this method could bring in a school education. It presents several examples of good practice from author's own experience.
Keywords: Methodology of history; Oral history; Ego-history; History of everyday life